Homogenization of immiscible compressible two-phase flow in double porosity media - Latifa Ait Mahiout; Brahim Amaziane; Abdelhafid Mokrane; Leonid Pankratov (Electronic journal of differential equations, 2016)
A double porosity model of multidimensional immiscible compressible two-phase flow in fractured reservoirs is derived by the mathematical theory of homogenization. Special attention is paid to developing a general approach to incorporating compressibility of both phases. The model is written in terms of the phase formulation, i.e. the saturation of one phase and the pressure of the second phase are primary unknowns. This formulation leads to a coupled system consisting of a doubly nonlinear degenerate parabolic equation for the pressure and a doubly nonlinear degenerate parabolic diffusion-convection equation for the saturation, subject to appropriate boundary and initial conditions. The major difficulties related to this model are in the doubly nonlinear degenerate structure of the equations, as well as in the coupling in the system. Furthermore, a new nonlinearity appears in the temporal term of the saturation equation. The aim of this paper is to extend the results of [9] to this more general case. With the help of a new compactness result and uniform a priori bounds for the modulus of continuity with respect to the space and time variables, we provide a rigorous mathematical derivation of the upscaled model by means of the two-scale convergence and the dilatation technique.